IMPLEMENTASI STRATEGI KONFLIK KOGNITIF DALAM PEMBELAJARAN IPS UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA DI MTS MIFTAHUL ULUM LUMAJANG - Hasan Husni (Jurnal Penelitian dan Pendidikan IPS, 2016)
This study aims to assess the application of learning strategies cognitive conflict in the subject of population problems in Indonesia to improve students' critical thinking skills Eighth grad Islamic Junior High School of Miftahul Ulum Lumajang. This quantitative research using Quasi experiment design. The entire study population all of student eighth grade students Islamic Junior High School of Miftahul Ulum Lumajang at the year 2015/2016 which are 64 students. class sample VIII B and which are 32 students. Instrument research in the form of test description for the pre-test and post-test to measure students critical thinking skills. Data were analyzed using the One Sample t-test (mean difference test) to check the hypothesis. However, to analyze data research such as analysis of the validity, reliability, test for normality, homogenity of variance with SPSS 20.0 software for windows. Results of analysis of data obtained by the mean pretest control group = 42.97, and the experimental group = 45.19, for critical thinking skills. While the mean post-test control group and the experimental group = 74 718 = 82.44 ,. T-count value post-test two research groups that produce sig (2-tailed) = 0.000 which means <0,05 so that H0 is rejected. Conclusion The application of learning Cognitive Conflict Strategy feasible to use Social studies in Learning Ability To Enhance Critical Thinking the students of Islamic Junior High School Miftahul Ulum Lumajang.